2014
DOI: 10.1080/24748668.2014.11868721
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of success in English domestic Twenty20 cricket

Abstract: The purpose of this study was to investigate the determinants of success in Twenty20 cricket. 29 matches for winning teams and 30 matches for losing teams were analysed from the 2010 English domestic Twenty20 competition. Magnitude-based inferences, reported as effect sizes (ES), were used to characterise differences in performance indicators between winning and losing teams. The top 5 indicators of success were losing less wickets in the powerplay overs (ES = -1), losing less wickets between overs 7-10 (ES = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Fifty plus run batting partnerships have been found to distinguish winning and losing teams in Twenty20 cricket (Petersen, et al, 2008b;Douglas and Tam, 2010;Najdan, 2014). Such partnerships are also important in one day cricket.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty plus run batting partnerships have been found to distinguish winning and losing teams in Twenty20 cricket (Petersen, et al, 2008b;Douglas and Tam, 2010;Najdan, 2014). Such partnerships are also important in one day cricket.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous performance analysis hardware and software improvements also increased coaches' demand for data and information (Lyons, 2005, Groom et al, 2011. The use of improved available data is still in its infancy, but increasing at a brisk progress especially within the sport of cricket (Najdan et al, 2014). In this regard, elite coaches direct the data collection process and obtain specific information related to their own identified key performance indicators (Wright et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…6 Other researchers applied similar methods of quantifying the influence of the KPIs in the ICC World Twenty20 Cup tournament in 2009 7 and in the English domestic Twenty20 competition. 8,9 More recent notational analysis has included pitchlevel analysis data, including the line and length of wickets taken and boundaries scored. [8][9][10] A major limitation of these data is the number of variables that should be coded, such as the handedness of the bowler and batter, the side of the wicket the ball is delivered from, the type of bowler (pace), and the number of distinct lines and lengths classified.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 More recent notational analysis has included pitchlevel analysis data, including the line and length of wickets taken and boundaries scored. [8][9][10] A major limitation of these data is the number of variables that should be coded, such as the handedness of the bowler and batter, the side of the wicket the ball is delivered from, the type of bowler (pace), and the number of distinct lines and lengths classified. Moore et al 8 investigating seven matches of English domestic Twenty20 from the 2010 season found that the pitchlevel analyses were in-conclusive with no clear trends in boundary destination or the line and length of where boundaries are hit from.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation